Efeitos da sobrecarga crônica de ferro sobre a reprodutividade de camundongos - Alexandre, Jandinay Gonzaga (2022)
Iron is an essential metal for body homeostasis, acquired from a diet rich in red meat and grains and vegetables, but iron overload (chronic Fe) can cause damage to organs such as the heart, vessels, liver, pancreas and , also, in the organs of the reproductive system. Studies evaluating the effects of iron overload on the hypothalamic-pituitary-gonadal (HPG) axis in the literature are particularly scarce. The objective of this dissertation is to study the effects of chronic iron overload on the reproductive system and reproductive capacity of female mice. We used female mice (C57BL/6) and two experimental groups, control and Fe 10 mg/Kg. The animals destined to the Fe group received intraperitoneal (i.p) injections of iron-dextran (10mg/kg/day, 5x/week), while the animals in the control group received saline solution (0.9% NaCl) in the same volume, conditions and time period. Consecutively, for 30 days, the estrous cycle of the animals was evaluated through a vaginal smear properly stained with methanol, hematoxylin and eosin. At the end of the exposure, a reproductive assay was performed with some animals and other animals were anesthetized and euthanized for removal and consequently obtaining the organs involved in the hypothalamic-pituitary-gonadal axis for analysis. In our results, it was possible to identify a decrease in the size of the ovary, uterus and hypothalamus. It was also noticeable the accumulation of iron in the liver, spleen, hypothalamus, ovary and uterus. The estrous cycle of mice was deregulated. The histology of the ovaries showed impaired follicular development, with a numerical reduction of corpus luteum and an increase in the number of atretic follicles. Histology showed uterine hypotrophy. Even with Fe suppression, the estrous cycle was not normalized and when we quantified the litter, no pups were registered in the cages of animals belonging to the Fe group. These results suggest that chronic exposure to iron generated hemosiderosis, harming the organs involved in the hypothalamic-pituitary-gonadal axis, promoting a reduced or non-existent reproductive rate.